Refugee camps: fieldwork strategies on the Bangladesh-Myanmar border - Farzana, Kazi Fahmida (Academic Research Publishing Group, 2018)
The Rohingya refugees have been living in Bangladesh for over two decades. Temporary encampment turned out to be a permanent situation for many of them living in registered and unregistered refugee camps. The government of Bangladesh prohibits visitors‟ access in those camps without prior official permission. The bureaucratic hurdles for securing permission for a non-party individual to the refugee issue were lengthy, conspicuous, difficult, uncertain and risky, and involves going through layers of administration located in different places. This paper draws fieldwork experiences among registered and unregistered refugees from the Bangladesh side of the border. It shed some light on practicalities and sensitivities in the field and the challenges faced by a female researcher in a fieldwork setting in this remote borderland. It suggests various strategies and negotiations that granted access to various communities.